2021
DOI: 10.3233/jad-210277
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-National Study of Dementia Stigma Among the General Public in Israel and Australia

Abstract: Background: Despite the increasing amount of research on dementia stigma, there is a dearth of cross-national studies conducted on this subject. This is surprising since the experience of stigma is closely associated to socio-cultural aspects. Objective: The present study intended to expand knowledge about the impact of culture on dementia stigma by comparing the level and correlates of stigmatic beliefs about dementia among the general public in Israel and Australia. Methods: A cross-sectional study using an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 46 publications
1
7
1
4
Order By: Relevance
“…Dementia worry was found to be relatively low in both countries, as the average score was 1.78 and 1.67 for Israel and Australia, respectively, out of a 1–5 range, although it was significantly higher in Israel than in Australia, supporting our first hypothesis. Moreover, as hypothesized and similar to previous studies [ 5 , 6 , 7 , 34 , 35 , 36 ], positive and statistically significant associations were observed between dementia worry and knowledge of dementia, self-perceived dementia risk, ageism, and dementia stigma in both samples. However, contrary to our expectations, the interaction effects for dementia worry level by country were insignificant.…”
Section: Discussionsupporting
confidence: 90%
“…Dementia worry was found to be relatively low in both countries, as the average score was 1.78 and 1.67 for Israel and Australia, respectively, out of a 1–5 range, although it was significantly higher in Israel than in Australia, supporting our first hypothesis. Moreover, as hypothesized and similar to previous studies [ 5 , 6 , 7 , 34 , 35 , 36 ], positive and statistically significant associations were observed between dementia worry and knowledge of dementia, self-perceived dementia risk, ageism, and dementia stigma in both samples. However, contrary to our expectations, the interaction effects for dementia worry level by country were insignificant.…”
Section: Discussionsupporting
confidence: 90%
“…[36][37][38] It implied that effacing the stigma is the prerequisite of establishing a harmonious physician-patient relationship. Based on previous studies, males showed significantly higher stigma toward mentally ill patients, dementia patients, and drug addicts than females, [39][40][41] suggesting that gender differences might exist in the PPOSS. Measurement invariance across gender is the premise of comparing group differences.…”
Section: Discussionmentioning
confidence: 93%
“…The effect of education in our study could have been underestimated, as two-fifths of the participants had completed education at university or graduate school level, compared to 14.7% of women in a 2017 national sample [53]. Although most nations are facing the COVID-19 pandemic, the initial level of dementia-related stigma may vary across countries [54]. Because we did not use other instruments that are already established for measuring dementia-related stigma, the level of stigma among our participants could not be compared to that in other studies.…”
Section: Strengths and Limitationsmentioning
confidence: 99%